Member of Scientific Committee - Kyriakidis, Phaedon (My University, 2026)
Reviewed full and short paper submissions for AGILE 2024, the 27th AGILE Conference on Geographic Information Science, Glasgow, UK, June 4-7. https://agile-gi.eu/conferences/agile-gi-conferences/agile-2024-glasgow/committees-2024